(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: The COVID‐19 pandemic has generated a lot of interest among doctors as well as scientists around the world. Studies on the impact of the Covid‐19 pandemic, including in people with post SCI sufferance, are ongoing, aiming to understand the pathophysiological mechanisms of SARS‐ CoV2 in target tissues, to optimize related methods of diagnosis and treatment in both, initial and later phases of the disease – e.g.: ”long Covid” status – and thus, to make a substantial contribution to the quality of life improvement of the affected patients. After using the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (acronym PRISMA) method to quest for afferent knowledge, it resulted a quite small number (12) of articles, most of them indirectly approaching this topic. Therefore, is important to deepen this niche – which is scarcely approached – in order to find new therapeutic approaches able to combat COVID‐19‐ associated to SCI manifestations – like, for instance, to check whether the principle of intermittent hypoxia treatment is effective and worth to be included in the rehabilitation treatment protocols – as neither an indubitable effective drug or vaccine, or respectively, cure for SCI, has been provided so far. Keywords: Spinal cord injury, Paraplegia, Tetraplegia, COVID‐19, intermittent hypoxia treatment